Factors associated with preventive behaviours of COVID-19 among hospital staff in Iran in 2020: an application of the Protection Motivation Theory. Issue 3 (July 2020) - Bashirian, S.; Jenabi, E.; Khazaei, S.; Barati, M.; Karimi-Shahanjarini, A.; Zareian, S.; Rezapur-Shahkolai, F.; Moeini, B.
SUMMARY: This study was conducted to predict the preventive behaviours of healthcare workers (HCWs) towards COVID-19 based on the Protection Motivation Theory (PMT). This cross-sectional and analytical study was conducted on 761 HCWs in Hamadan, Iran, using multi-stage random sampling. The preventive behaviours against COVID-19 among HCWs were assessed at a relatively desirable level. Based on the PMT, threat and coping appraisal were predictors of protection motivation to conduct COVID-19 preventive behaviours ( P <0.001). The intention was also predictive of COVID-19 preventive behaviours ( P <0.001). Consideration of personnel's self-efficacy and their knowledge regarding the effectiveness of protective behaviours in designing staff training programmes are recommended.